Attention Deficit Hyperactivity Disorders Symptomatology Among Individuals With Down Syndrome. Issue 1 (March 2014) - Edvardson, Simon; Msallam, Nadira; Hertz, Pnina; Malkiel, Sarah; Wexler, Isaiah D.; Tenenbaum, Ariel
Abstract The prevalence of attention deficit hyperactivity disorders (ADHD) among individuals with Down syndrome (DS) has been difficult to ascertain. This is because many of the phenotypic features of DS may resemble the clinical manifestations of DS and the myriad methodological challenges in diagnosing ADHD in children with intellectual disabilities (ID). With this in mind, the authors set to determine the prevalence of ADHD symptomatology in a cohort of children and young adults in a DS clinic. Subjects were 83 children and adults, ages 5–38, who were attending the Down Syndrome Center at the Hadassah Mount Scopus University Medical Center. All were screened for ADHD. Screening methods included review of medical files, telephone interviews, and use of the ADHD module of the Autism‐Tics, Attention‐Deficit/Hyperactivity disorder, and other Comorbidities questionnaire. It was found that 26 (31.3%) of the subjects fulfilled the Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev.) criteria for ADHD. Of these, 17 (65.4%) were diagnosed as predominantly inattentive type. Four (15.4%) were predominantly impulsive‐hyperactive, and five (19.2%) had the combined type. No statistically significant association was found between ADHD and age, sex, number of siblings, presence of heart disease, thyroid dysfunction, sleep disorders, or a family history of ADHD. The prevalence of ADHD symptomatology among individuals with DS in this representative sample is high compared with the general population. ADHD may be underdiagnosed in this special population, hence the need for systematic screening.